A low-temperature, environment-friendly approach to the synthesis of magnesium borates using magnesium waste scraps - Kaplan, Aycin; Kipcak, Azmi Seyhun; Senberber, Fatma Tugce; Derun, Emek Moroydor; Piskin, Sabriye (WALTER DE GRUYTER GMBH, 2015)
In the present study, magnesium borate synthesis was performed by a hydrothermal mixing method, with the use of magnesium waste scraps (W) as the magnesium source, along with boric acid (H) or boron oxide (B) as the boron source. For an environment-friendly approach, a solid waste of magnesium was used at low reaction temperatures. Results of X-ray diffraction analyses showed that admontite [MgO(B2O3)(3)center dot 7(H2O)] and mcallisterite [Mg-2(B6O7(OH)(6))(2)center dot 9(H2O)] types of magnesium minerals were obtained from the synthesis. Through Fourier transform infrared spectroscopy and Raman spectroscopy, in both the infrared and the visible regions, characteristic borate bands were observed. The results of the boron oxide content analyses were in agreement with literature data. The particle sizes, obtained by scanning electron microscopy analyses, were found within the range of 200 nm to 2 mu m for mcallisterite and 210 nm to 2.5 mu m for admontite minerals. The reaction yields of the minerals were calculated in the range of 16.6-82.0% for the experiments on waste magnesium and boric acid, whereas for the experiments on waste magnesium and boron oxide these were 12.7-78.8%.
Keywords: environment friendly; hydrothermal; magnesium borate; magnesium waste; METAL; Chemistry